Strategies to improve membrane performance in wastewater treatment - Ahmed S.F.; Mehejabin F.; Momtahin A.; Tasannum N.; Faria N.T.; Mofijur M.; Hoang A.T.; Vo D.-V.N.; Mahlia T.M.I. (Elsevier Ltd, 2023)
Biological water treatment; Bioreactors; Chemical cleaning; Cost effectiveness; Effluents; Membrane fouling; Membrane technology; Microfiltration; Phosphorus; Reclamation; Reverse osmosis; % reductions; Fouling control; Health benefits; Hybrid techniques; Membrane bioreactor; Membrane filtrations; Membrane performance; Membrane process; Pre-treatments; Safe water; Wastewater treatment; adsorbent; ammonia; nitrogen; phosphorus; water; adsorption; bioreactor; bubble; fouling; membrane; mitigation; public health; reverse osmosis; wastewater treatment; activated sludge; Article; controlled study; distillation; filtration; fouling control; membrane technology; osmosis; pervaporation; public health; reverse osmosis; sewage effluent; waste water management